Implementasi Pembelajaran Berbasis Proyek dalam Mata Pelajaran Seni Budaya melalui Makrame Kelas V SD 2 Purworejo - Zidny Naila Nur Rosyida; Nafisa Dwi Rahma; Putri Dewi Safitri; Shofia Sri Jayanti; Rakanita Dyah Ayu Kinesti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2026)
This study aims to analyze the implementation of the Project-Based Learning (PjBL) model in Cultural Arts learning through macrame craft activities for fifth-grade students at SD 2 Purworejo. A qualitative descriptive method was employed, involving the Cultural Arts teacher and fifth-grade students as research subjects. Data were collected through observation, interviews, and documentation during the learning process. The results indicate that the implementation of PjBL through macrame projects was effective and carried out through systematic stages, including preparation, demonstration, practice, refinement, and reflection. Students demonstrated active participation, good collaboration, and improvement in creativity and fine motor skills.